Age and marital status are major factors associated with institutionalisation in elderly Hong Kong Chinese. Issue 3 (June 1994) - Woo, J; Ho, S C; Lau, J; Yuen, Y K
Abstract : STUDY OBJECTIVE–To determine the need for long term institutional care for elderly Chinese living in Hong Kong and factors associated with institutional living. DESIGN–Survey by interviewer administered questionnaire of a stratified random sample of all recipients of old age or disability allowance covering 90% of the population. SETTING–Survey performed in Hong Kong, a city on the south coast of China with an area of 1070 km2 and approximately six million people. PARTICIPANTS–A total of 2032 subjects aged 70 years and over (999 men, 1033 women) participated. MAIN RESULTS–Overall, 16% of the elderly live in institutions. The percentage is higher in women and in the older age group (81% for those aged 80 years and over). After adjusting for age and sex, the following factors were positively associated with institutionalisation: poor cognitive function, measures of functional disability, poor vision, Parkinson's disease, stroke, and past fractures. Multivariate analysis identified age and marital status as associated factors with the highest odds ratio (13.6 and 7.1 respectively), followed by various disability indicators. CONCLUSION–The survey shows that requirements for long term care places are unlikely to be much affected by preventive measures, and would need to increase by about 30% by 2000 to cope with the projected increase in the number of elderly aged 70 years and over. Measures to provide sufficient trained personnel and policy for regulation of standards should be made.